Senescence and Type 2 Diabetic Cardiomyopathy: How Young Can You Die of Old Age? - Henson, Sian M.; Aksentijevic, Dunja (Frontiers in Pharmacology, 2021)
Inflammation is well understood to be a physiological process of ageing however it also underlies many chronic diseases, including conditions without an obvious pathogenic inflammatory element. Recent findings have unequivocally identified type 2 diabetes (T2D) as a chronic inflammatory disease characterized by inflammation and immune senescence. Immunosenescence is a hallmark of the prolonged low-grade systemic inflammation, in particular associated with metabolic syndrome and can be a cause as well as a consequence of T2D. Diabetes is a risk factor for cardiovascular mortality and remodelling and with particular changes to myocardial structure, function, metabolism and energetics collectively resulting in diabetic cardiomyopathy. Both cardiomyocytes and immune cells undergo metabolic remodelling in T2D and as a result become trapped in a vicious cycle of lost metabolic flexibility, thus losing their key adaptive mechanisms to dynamic changes in O2 and nutrient availability. Immunosenescence driven by metabolic stress may be both the cause and key contributing factor to cardiac dysfunction in diabetic cardiomyopathy by inducing metabolic perturbations that can lead to impaired energetics, a strong predictor of cardiac mortality. Here we review our current understanding of the cross-talk between inflammaging and cardiomyocytes in T2D cardiomyopathy. We discuss potential mechanisms of metabolic convergence between cell types which, we hypothesize, might tip the balance between resolution of the inflammation versus adverse cardiac metabolic remodelling in T2D cardiomyopathy. A better understanding of the multiple biological paradigms leading to T2D cardiomyopathy including the immunosenescence associated with inflammaging will provide a powerful target for successful therapeutic interventions.